2022
DOI: 10.1080/17483107.2022.2121008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mobility scooter on occupational participation among older adults in Singapore: an exploratory study

Abstract: PURPOSE With rapid ageing, the use of mobility scooters by community-dwelling older adults with mobility limitations has been increasingly prevalent in Singapore. Their experiences in using mobility scooters remain unclear. This study aimed to explore the impact of mobility scooters on occupational performance and engagement among elderly Singaporeans. MATERIALS AND METHODSMobility scooter users were recruited via purposive and snowballing sampling. Semi-structured interviews were conducted in English or Manda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Sund and Brandt (2018) reported that satisfaction with a PMD and frequency of use is high for general users. For older adults with reduced mobility, a PMD enhanced community participation and increased independence despite barriers within the built environment (Lim et al, 2022). There is limited research regarding the use of a PMD for those with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Sund and Brandt (2018) reported that satisfaction with a PMD and frequency of use is high for general users. For older adults with reduced mobility, a PMD enhanced community participation and increased independence despite barriers within the built environment (Lim et al, 2022). There is limited research regarding the use of a PMD for those with obesity.…”
Section: Introductionmentioning
confidence: 99%